Is PiSS Alpha-1 Antitrypsin Deficiency Associated with Disease?. (6th June 2010) - McGee, Dawn; Schwarz, Laura; McClure, Rebecca; Peterka, Lauren; Rouhani, Farshid; Brantly, Mark; Strange, Charlie
Abstract : Background . Alpha-1 antitrypsin deficiency (AAT) is an inherited condition that predisposes to lung and/or liver disease. Objective . The current study examined the clinical features of the PiSS genotype. Methods . Nineteen study participants (PiSS) and 29 matched control participants (PiMM) were telephone interviewed using a standardized questionnaire. Demographic features, cigarette smoking, vocation, medication history, and clinical diagnoses were compared. Statistical analysis was performed. Finally, a comprehensive literature review was performed by two investigators. Results . 12/19 (63.2%) study participants reported the presence of lung and/or liver disease compared to 12/29 (41.4%) control participants. There trended toward having a higher frequency of medication allergies in the study population (42.11% versus 20.69%). Conclusions . The PiSS genotype was associated with a similar incidence of obstructive lung disease to controls. Selective bias intrinsic in testing for AAT deficiency and the rarity of the PiSS genotype will make future study of this association dependent on population-based tests.